Hypervisibility in Australian punk scenes: Queer experiences of spatial logics of gender and sexuality. (1st October 2019) - Sharp, Megan
In this article, I draw on the knowledge and lived experience of queer people – some of whom also identify as trans, gender diverse and/or non-binary – who actively participate in Australian punk scenes. Using socio-geographical research of intersectionality, critical race theory and spatiality I find queer experiences of and in punk highlight a complication to claims of female and queer invisibility, one that takes into account spacial formations. Attending to queer, trans and gender-diverse people's experiences, hypervisibility presents a conceptual entanglement where genders, bodies and sexualities attract attention from a dominant, patriarchal group, rather than being rendered invisible by it. This hypervisibility appears steeped in unintelligibility where being visible but unknowable presents a range of issues such as standing out not only in physical punk spaces such as gigs, but on digital platforms and in everyday life. As such, this article builds on a feminist thesis of invisibility politics by aiming to elasticize knowledges of gender, resistance and subcultural participation among marginalized groups.